제주흑우 동결정액 제조에 있어 난황 Tris 희석제에 항산화제로서 Taurine, Hypotaurine 그리고 Trehalose의 첨가가 동결 융해 후 정자의 성상에 미치는 영향 - 오신애; 고민희; 강태영; 최선호; 고문석; 정영호; 조원모; Oh, Shin-Ae; Ko, Min-Hee; Kang, Tae-Young; Choi, Sun-Ho; Ko, Moon-Suck; et al. (Journal of animal science and technology, 2012)
Cryopreservation induces sublethal damage to the spermatozoa, which leads to their reduced fertile life. The objective of this study was to investigate the effect of taurine, hypotaurine and trehalose as antioxidants on the function of the freezing-thawed sperm in Korean Jeju Black Bull. The semen was cryopreserved with tris egg yolk extendercontaining 7% glycerol and treated with 20mM taurine, hypotaurine and trehalose. Frozen-thawed sperms were evaluated for sperm motility, viability, membrane integrity, acrosome integrity and sperm penetration ability. The results were compared to semen cryopreserved in tris egg yolk extender containing 7% glycerol only as control. Frozen-thawed semen evaluation clearlyindicated that the addition of taurine or hypotaurine significantly improved (p<0.05) the motility and viability compared to control spermatozoa. Moreover, in membrane integrity, swollen sperm ratio was significantly increased (p<0.05) in taurine, hypotaurine or trehalose compared to control. In sperm acrosome integrity, F pattern ratio was increased (p<0.05) in hypotaurine among treatments, and AR pattern was significantly lowered (p<0.05) in taurine, hypotaurine and trehalose. In assessed sperm fertilizing ability, taurine, hypotaurine or trehalose significantly improved (p<0.05) the ratio of pronucleus formation and SFI. Finally, compared with the control, addition of taurine, hypotaurine or trehalose as an antioxidant to the freezing extender showed more positive effects on the frozen-thawed spermatozoa. It is concluded that the addition of taurine, hypotaurine, or trehalose to the freezing extender could reduce cryodamage of the Korean Jeju Black Bull spermatozoa. 제주흑우의 동결 정액 제조시 동결 보존액에 첨가한 taurine과 hypotaurine은 동결 융해 후 정자의 운동성, 생존성 그리고 정자막 온전성을 개선시키는 것을 알 수 있었다. Taurine과 hypotaurine의 첨가는 유의적으로 높은 운동성, 생존성을 보였으며(p<0.05), 특히 hypotaurine은 다른 실험구에 비하여 유의적으로 높은 정자막 온전성을 나타냈다(p<0.05). 뿐만 아니라, hypotaurine은 유의적으로 높은 F pattern 비율을 유지하였으며(p<0.05), 이들 항산화물질을 첨가한 실험구에서는 대조구에 비하여 유의적으로 낮은 AR pattern을 나타내어(p<0.05) 동결로 기인된 수정능획득 유사 상태 정자의 비율을 유의적으로 감소시켜 조기 첨체반응 비율을 감소시켰다. 정자의 난자내 침투능력에 있어서 모든 처리구에서 대조구보다 높은 웅성전핵 형성율과 SFI를 나타냈으며, hypotaurine의 처리는 가장 높은 침투능력을 나타냈으나 처리구간의 유의적 차이는 나타나지 않았다. 본 연구결과는 멸실위험의 토종가축 생식세포 및 유전자원 보존과 토종가축 육성을 위한 번식 증대를 위한 제주흑우 동결정액 제조에 중요한 이용 방법이 될 것이며, 동결 융해 후 정자의 기능 개선을 위한 다양한 희석제 및 첨가제를 활용한 연구가 필요할 것으로 사료된다.